2014
DOI: 10.1111/icad.12067
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Ichneumonidae (Insecta: Hymenoptera) in a protected area of Central Spain: What are we protecting?

Abstract: Invertebrates are rarely considered when designing protected areas, and their biodiversity patterns in these areas are almost always unknown. We studied the spatial and temporal diversity of Ichneumonidae in five selected habitats of Cabañeros National Park: grazing pastureland, shrubland, and three types of woodland (Pyrenean oak, cork oak, and ash woodlands). We focused on 11 subfamilies, with species classified into trophic guilds. The highest diversity and richness of Ichneumonidae were found in ash woodla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
1
6
2
Order By: Relevance
“…These results largely agree with those obtained previously in the RBRL by Gonzalez-Moreno et al (2010) in a study on Cremastinae and Labeninae (Ichneumonidae), who reported the highest species richness in the dry forest, and by González-Moreno et al (2015) on Cryptinae (Ichneumonidae), who also found the highest values of abundance and diversity in the dry forest. However, our results appear to contradict those reported by Chay-Hernández et al (2006) and Mazon & Bordera (2014), who identified the highest diversity of ichneumonids in open areas surrounded by natural forest, which may be favoured because these areas allow them to pass from one habitat to another, acting as biological corridors (Haddad et al , 2003). However, in this case, a more open savannah is also a harsh environment with higher temperature and humidity fluctuations, leading to further reductions in insect biodiversity (Gauld, 1987; Shapiro & Pickering, 2000).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results largely agree with those obtained previously in the RBRL by Gonzalez-Moreno et al (2010) in a study on Cremastinae and Labeninae (Ichneumonidae), who reported the highest species richness in the dry forest, and by González-Moreno et al (2015) on Cryptinae (Ichneumonidae), who also found the highest values of abundance and diversity in the dry forest. However, our results appear to contradict those reported by Chay-Hernández et al (2006) and Mazon & Bordera (2014), who identified the highest diversity of ichneumonids in open areas surrounded by natural forest, which may be favoured because these areas allow them to pass from one habitat to another, acting as biological corridors (Haddad et al , 2003). However, in this case, a more open savannah is also a harsh environment with higher temperature and humidity fluctuations, leading to further reductions in insect biodiversity (Gauld, 1987; Shapiro & Pickering, 2000).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results coincide with those of Mazon & Bordera (2014), who found that phytophagous parasitoids are the most abundant guild in Spanish forests. It has been estimated that there are five to six species of parasitoid for every phytophagous insect (Askew & Shaw, 1986; Hawkins & Lawton, 1987).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding overall functional diversity, it was significantly higher in the low conservation areas of two reserves. Although it can not be seen as a consistent pattern, open areas may serve as corridors for insects (Mazón and Bordera 2014;Gutiérrez-Chacón et al 2020) connecting well-conserved forests, and therefore these more disturbed areas would have more diverse assemblages. Also, by being embedded in a conserved matrix, these areas may be acting as ecotones, which may harbor a higher diversity of Hymenoptera than the forests, as seen for ants (Coelho and Ribeiro 2006), bees (Polatto and Alves 2020; Theodorou et al 2020) and parasitoids (Rossetti et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of hymenopteran communities is known to differ from habitat to habitat (Jäkel & Roth 2004;Fraser et al 2007;Mazón & Bordera 2014;Kendall & Ward 2016). In addition, hymenopteran parasitoid species generally occur at low densities and are more vulnerable to environmental degradation than insect species of lower trophic levels (LaSalle & Gauld 1991;LaSalle 1993;Shaw & Hochberg 2001;Tscharntke et al 2002;Shaw 2006;Fraser et al 2008).…”
Section: Introductionmentioning
confidence: 99%